2023
DOI: 10.1021/acs.analchem.2c05071
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry-Based Charge Heterogeneity Characterization of Therapeutic mAbs with Imaged Capillary Isoelectric Focusing and Ion-Exchange Chromatography as Separation Techniques

Abstract: Imaged capillary isoelectric focusing (icIEF) and ionexchange chromatography (IEX) are two essential techniques that are routinely used for charge variant analysis of therapeutic monoclonal antibodies (mAbs) during their development and in quality control. These two techniques that separate mAb charge variants based on different mechanisms and IEX have been developed as front-end separation techniques for online mass spectrometry (MS) detection, which is robust for intact protein identification. Recently, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although more time-consuming and labor-intensive, off-line fractionation is not limited to the separation of analytes requiring only MS-compatible components and may be necessary to fully characterize some highly complex proteins at the intact level. The new preparative iCIEF instrument allows simultaneous isolation and characterization of individual protein charge variants and can be directly connected to MS to deliver the fractionated protein samples for characterization [167][168][169][170]. During pressure mobilization, an electric field keeps the samples in the separation capillary focused.…”
Section: Cief and Imaged Ciefmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more time-consuming and labor-intensive, off-line fractionation is not limited to the separation of analytes requiring only MS-compatible components and may be necessary to fully characterize some highly complex proteins at the intact level. The new preparative iCIEF instrument allows simultaneous isolation and characterization of individual protein charge variants and can be directly connected to MS to deliver the fractionated protein samples for characterization [167][168][169][170]. During pressure mobilization, an electric field keeps the samples in the separation capillary focused.…”
Section: Cief and Imaged Ciefmentioning
confidence: 99%
“…The established methodology was employed for the charge heterogeneity characterization of pembrolizumab [169] and for commercial monoclonal antibodies (mAbs) and antibody-drug-conjugates [170]. Wu et al [168] recently compared this innovative iCIEF-MS approach for charge variant analysis of diverse mAbs to strong cation exchange-MS. It was found that iCIEF-MS outperformed strong cation exchange-MS in this study by demonstrating its outstanding sensitivity, low carryover, accurate protein identification, and higher separation resolution.…”
Section: Ce-ms Analysis Of Peptide-and Protein-based Therapeuticsmentioning
confidence: 99%
“…Capillary isoelectric focusing is a powerful analytical technique that provides efficient separation of zwitterionic compounds in accordance with their Isoelectric Points (pI). , The process of cIEF includes two steps; focusing and mobilization. Focusing involves the establishment of a pH gradient along the capillary and pI-controlled redistribution of the analytes, while mobilization provides delivery of the focused analytes to the point of detection.…”
Section: Introductionmentioning
confidence: 99%